Adolescent disclosure and concealment: Longitudinal and concurrent associations with aggression. Issue 5 (29th May 2013) - Leavitt, Chelom E.; Nelson, David A.; Coyne, Sarah M.; Hart, Craig H.
Abstract This longitudinal study assessed the association between prior (preschool) and concurrent physical and relational aggression as they relate to Russian adolescents' disclosure and concealment patterns with their parents. In the initial preschool study, there were 106 boys and 106 girls (mean age = 60.24 months, SD = 7.81). Both peer nominations and teacher ratings of aggression were obtained for these children. Ten years later, the majority of these children (72.2%; n = 153) completed a longitudinal follow‐up battery of assessments. Included in these measures was a self‐reported measure of aggression as well as an assessment of the extent to which these adolescents disclosed to and concealed information from their parents. Separate models were estimated by gender of child for the 153 children who participated in both Time 1 and Time 2 data collections. Preschool physical aggression proved an important longitudinal predictor of adolescent disclosure and concealment for girls. Concurrently, self‐rated relational aggression was also significantly associated with concealment for both boys and girls. Aggr. Behav. 39:335–345, 2013. © 2013 Wiley Periodicals, Inc.